Establishment of a new reverse genetics system for respiratory syncytial virus under the control of RNA polymerase II - Takahashi, Tatsuki; Ueno, Shiori; Sugiura, Yoshiro; Shimizu, Kenta; Kamitani, Wataru (Microbiology and immunology, 2023)
A reverse genetics system for the respiratory syncytial virus (RSV), which causes acute respiratory illness, is an effective tool for understanding the pathogenicity of RSV. To date, a method dependent on T7 RNA polymerase is commonly used for RSV. Although this method is well established and recombinant RSV is well rescued from transfected cells, the requirement for artificial supply of T7 RNA polymerase limits its application. To overcome this, we established a reverse genetics system dependent on RNA polymerase II, which is more convenient for the recovery of recombinant viruses from various cell lines. First, we identified human cell lines with high transfection efficiency in which RSV can replicate effectively. Two human cell lines, Huh-7 and 293T, permitted the propagation of recombinant green fluorescent protein-expressing RSV. Our minigenome system revealed that efficient transcription and replication of RSV occurred in both Huh-7 and 293T cells. We then confirmed that recombinant green fluorescent protein-expressing RSV was rescued in both Huh-7 and 293T cells. Furthermore, the growth capability of viruses rescued from Huh-7 and 293T cells was similar to that of recombinant RSV rescued using the conventional method. Thus, we succeeded in establishing a new reverse genetics system for RSV that is dependent on RNA polymerase II.